2006
DOI: 10.1007/s10725-006-0021-7
|View full text |Cite
|
Sign up to set email alerts
|

Salinity-induced changes in two cultivars of Vigna radiata: responses of antioxidative and proline metabolism

Abstract: The effects of amino acid cysteine to culture systems of microspore-derived callus induction as well as plantlet regeneration were studied. Isolated pollen along with anther walls of basmati cultivars, Pusa basmati 1, Basmati 370 and Basmati 386 were cultured in a medium based on N 6 salts supplemented with or without cysteine following pollen embedment in agarose. The induction and regeneration medium with cysteine gave twice as effective androgenesis and plantlet regeneration in recalcitrant basmati rice cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 42 publications
7
41
1
Order By: Relevance
“…Results of Khan et al (2014) verified by this study as proline demonstrated a positive correlation with grain yield per plant (Fig. 4a), which indicates its potential to induce salt tolerance, might be due to its role in osmotic adjustment and stabilizing the structure of organelles and macromolecules (Sumithra et al, 2006). Like proline, glycine betaine is also considered to play a crucial role in salinity tolerance by protecting plant cells through osmotic adjustment (Raza et al, 2006), stabilizes proteins to secure the photosynthetic apparatus (Cha-um et al, 2010).…”
Section: Discussionsupporting
confidence: 74%
“…Results of Khan et al (2014) verified by this study as proline demonstrated a positive correlation with grain yield per plant (Fig. 4a), which indicates its potential to induce salt tolerance, might be due to its role in osmotic adjustment and stabilizing the structure of organelles and macromolecules (Sumithra et al, 2006). Like proline, glycine betaine is also considered to play a crucial role in salinity tolerance by protecting plant cells through osmotic adjustment (Raza et al, 2006), stabilizes proteins to secure the photosynthetic apparatus (Cha-um et al, 2010).…”
Section: Discussionsupporting
confidence: 74%
“…Sumithra et al, (2006) have reported increased SOD and CAT activity in NaCl tolerant cultivars in this species. There are previous reports indicating increased activity of SOD in pea (Hernandez, et al, 1993) wheat (Sairam, et al, 2003) cotton (Gossett, et al, 2004) potato (Queiros, et al, 2007) sweet potato (He, et al, 2008).…”
Section: Antioxidant Enzymesmentioning
confidence: 59%
“…MDA content of tolerant callus was less when compared to that of sensitive callus line ( Table-1). Sumithra, et al,2006) reported low levels of lipid peroxidation in salt tolerant V. radiata cv Pusa bold than in salt sensitive cv CO 4. Jain,et al,(200l) reported 4 fold increases in MDA content of sensitive callus of ground nut when grown on saline medium where as in the tolerant callus line the increase was only 1.1 fold.…”
Section: Lipid Peroxidationmentioning
confidence: 95%
“…Rahnama and Ebrahimzadeh, (2004) reported that salt stress caused a reduction in the activities of ProDH in all the cultivars (Solanum tuberosum), and such reduction in ProDH activity and the simultaneous increase in proline level have also been reported in Brassica juncea under salt stress (Madan et al, 1995). Sumithra et al, (2006) reported that the activities of P5CS and δ-OAT significantly increased with progressive increase in salinity stress. In contrast, the activity of ProDH significantly decreased with increasing salt stress in both cultivars (Vigna radiate).…”
Section: Discussionmentioning
confidence: 74%